Lime Rate in Clayey Soils Influences Chemical Fertility and Sugarcane Yield - de Campos, Murilo [UNESP]; Martello, Jorge Martinelli [UNESP]; de Siqueira, Gabriela Ferraz [UNESP]; Garcia, Ariani [UNESP]; Scudeletti, Daniele [UNESP]; Dias, Patrícia Pereira [UNESP]; Rossetto, Raffaella; Calonego, Juliano Carlos [UNESP]; Cantarella, Heitor; Crusciol, Carlos Alexandre Costa [UNESP] (MDPI, 2022)
Liming contributes to the alleviation of acidity in highly weathered soils. For sugarcane, the use of green harvest methods and new soil tillage systems requires an adjustment of lime application rates. In the present study, the effects of different lime rates and tillage systems on sugarcane performance and soil chemical fertility parameters were assessed. Three experiments were conducted in two locations between April 2015 and October 2019. The study design was a randomized block field study with four replicates. Four lime rates were applied once at sugarcane establishments in each soil tillage system and location: no liming (control); lime recommended rate (LRR); two times LRR (2× LRR); and three times LRR (3× LRR). The three soil tillage systems were conventional (CT), deep-strip (DT), and modified deep-strip tillage (MDT). Soil chemical fertility, leaf nutrient concentrations, and sugarcane yield components were analyzed, and correlations were identified by principal component analysis (PCA). The soil acidity was adequately alleviated in all tillage systems. Increasing the lime rate improved the lime distribution and soil fertility parameters. Applying lime at rates higher than LRR improved stalk and sugar yields, longevity, agronomic efficiency index (AEI), and correlated with a longer residual effect of liming, mainly in the last ratoon.
Keywords: conventional tillage; deep strip-tillage; furrower; localized tillage